INFORMAL SECTOR INVESTMENT AND EMPLOYMENT GENERATION IN BENUE STATE, NIGERIA - ABUR, CYPRIAN CLEMENT (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2020)
The study analysed the role of informal sector investment on employment generation in Benue state. The study employed modified ordinary least square model to analyze data. The result also shows that employment has an overall positive relationship with informal sector income, investment and employee’s education, this confirms to the apriori. By implication, it means that the increase in informal sector income, investment and education leads to employment in the informal sector investment in Benue State. The study concludes that the informal sector is made up of able-bodied people and are constrained with a myriad of challenges which may deter and limit the potential for alleviating unemployment. Furthermore, the informal sector suffers from social insecurity and so a policy framework must be formulated to attract youth in the sector.